(untitled) (Baghdad Science Journal, 2024)
This study was conducted in the Najaf Governorate- Iraq, to analyze biological samples from smokers and non-smokers. The samples, including blood serum, urine, hair, and nails, were used as biomarkers to determine uranium concentrations (UC) and isotopes (238U, 235U, and 234U). Using a natural exposure method, the nuclear track detector (CR-39, UK) was utilized to measure these Uc in the samples. Seventy-five samples of blood serum, urine, hair, and nails were collected for smokers of healthy people and fifty samples for non-smokers of healthy people in five age groups. This study was based on age and smoking to compare the results and determine their effects on the Uc. The results show that the average values of Uc in blood serum, urine, hair, and nails for smokers were 0.180±0.042 ppb, 0.759±0.024 ppb, 0.912±0.085 ppm, and 0.934±0.091 ppm, respectively. While, the average values of Uc in blood serum, urine, hair, and nails for non-smokers were 0.110±0.014 ppb, 0.157±0.023 ppb, 0.736±0.032 ppm, and 0.756±0.024 ppm, respectively. The results and comparisons indicate that all Uc depend on the variables on which this study was based (age and smoking). By comparing the Uc for all biological samples for smokers and non-smokers, the value of P-value was highly significant statistically which was <0.001. According to the results of the study samples, the mean values of UC, 238U, 235U, and 234U for biological samples in smokers were higher than in non-smokers. Thus, it may be said that cigarette smoking is used as a biomarker of the presence of Uc.